2018
DOI: 10.5114/fmpcr.2018.73703
|View full text |Cite
|
Sign up to set email alerts
|

The impact of paternal attachment training skills on the extent of maternal neonatal attachment in primiparous women: a clinical trial

Abstract: Background. Women in some social groups of the population may be less supported by their partners and may be more reliant on their employees. Objectives. This study was designed to investigate the impact of paternal-attachment training skills on the extent of maternal neonatal attachment in primiparous women referred to the hospitals affiliated with the Shiraz University of Medical Sciences. Material and methods. A randomized controlled trial was done in hospitals affiliated with the Shiraz University of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Women required support from their husband and extended family [31, 32]. Both first-time and second-time mothers expressed the hope that their husband and extended family members could be better equipped with the knowledge and skills needed for postpartum and baby care [33, 34]. It was suggested that if mothers and grandmothers agreed on childcare practices, this would facilitate the transition of postpartum women into motherhood and ease the stress felt by postpartum women [33, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Women required support from their husband and extended family [31, 32]. Both first-time and second-time mothers expressed the hope that their husband and extended family members could be better equipped with the knowledge and skills needed for postpartum and baby care [33, 34]. It was suggested that if mothers and grandmothers agreed on childcare practices, this would facilitate the transition of postpartum women into motherhood and ease the stress felt by postpartum women [33, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Setodeh et al (2018) in a study, which aimed to examine the effect of fathers’ education during pregnancy on the degree of maternal attachment to infants, reported that the fathers’ education was effective in improving maternal attachment to infants. The educational contents in the above study that were delivered in 4 sessions included familiarity with the concept of attachment and types of attachment skills, ways to control stress and anxiety, familiarity with mental and physical changes during pregnancy, and familiarity with the role of spouse to communicate with the fetus [ 39 ]. The differences in the results of the above and present studies can be due to teaching attachment behaviors to fathers, the use of different tools, and different measurement times in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This checklist was also cited by Setoudeh and Ghodrati as well as by other researchers. 31 - 35 All data were also collected by the researcher. In order to express the characteristics of the research units, descriptive statistics including frequency table, mean (SD) were used.…”
Section: Methodsmentioning
confidence: 99%